Pengaruh Pemberian Glukosa Oral Pra Operasi Terhadap Kadar Glukosa Darah pada Pasien Diabetes Melitus yang dilakukan operasi dengan anestesi Umum - Harahap, Dhiny Yolanda; Hanafie, Achsanuddin; Lubis, Andriamuri Primaputra; Amelia, Rina (Fakultas Kedokteran Universitas Trisakti, 2024)
Background The administration of general anesthesia during surgery can trigger the body’s stress response causing changes in regular metabolic patterns that result in hyperglycemia and ketosis. The goal of this study is to investigate how preoperative oral glucose and non-glucose administration affect patients with diabetes mellitus with blood glucose levels during surgery under general anesthesia. Methods This is a single-blind, randomized controlled trial (RCT) being carried out by the Central Surgical Installation and postoperative recovery area at Haji Adam Malik General Hospital Medan. The study sample consists of 38 patients with diabetes mellitus who underwent electively scheduled laparotomies under general anesthesia and met inclusion/exclusion criteria. For treatment group participants, mineral water containing 50 grams of glucose was administered with 400 cc. Research hypotheses were assessed using the t-test, and significant findings had p-values equal to or less than 0.05 within a confidence interval of 95%. Results The study sample had a mean age of 50.1 ± 12.73 and showed a significant effect between glucose levels before (178.47) and after (163.78) administration of maltodextrin, with a P value (0.001). No side effects were observed during or after the post-operative evaluation process conducted in this study's participants. Conclusions Patients with diabetes mellitus experience a preoperative oral glucose-induced impact on blood glucose levels.